Síntese e caracterização teórico-experimental das peroviskitas ABO3 (A = Sm, Eu e Gd e B = Ti, Cr, Ni e Cu) por reação de estado solido e altas pressões - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
High- and medium-entropy multicomponent systems based on perovskites enable the incorporation of different elements, allowing the customization of physical and chemical properties. The systems Sm(Ti₀.₁₇Cr₀.₂₃Ni₀.₃₀Cu₀.₃₀)O₃, Eu(Ti₀.₁₈Cr₀.₂₂Ni₀.₃₀Cu₀.₃₀)O₃, and Gd(Ti₀.₁₈Cr₀.₂₂Ni₀.₂₆Cu₀.₃₃)O₃ were synthesized by mechanical milling under ambient atmosphere. The structural evolution was monitored by X-ray diffraction (XRD), and Rietveld refinement confirmed the formation of orthorhombic perovskites (space group Pnma) with nanometric crystallite sizes (<20nm). No new phases were observed after heat treatment at 500 ºC. After obtaining the medium-entropy perovskites, we conducted a systematic study of these multicomponent materials using Density Functional Theory (DFT) calculations. The theoretical calculations employed lattice parameters and atomic positions determined experimentally. Due to the partial site occupancy and the high computational cost associated with very large supercells, we selected two configurations based on the ferromagnetic behavior of Cr and Ni elements. Based on the formation energy, we demonstrated the feasibility of obtaining medium-entropy perovskites. We calculated the band structure and the projected density of states (PDOS) with and without the inclusion of the 4f orbital to evaluate its effects. It is important to note that the compounds exhibit semiconducting behavior only in the spin-down state, which was not affected by the inclusion of the 4f orbital. Both configurations were subjected to hydrostatic pressures of up to 30 GPa, and the Birch-Murnaghan equation of state was used to calculate the compressibility modulus. Under pressure, the spin-down gap disappeared, with the extent of this change depending on the system. The compressibility modulus not only varies with the rare-earth element but also depends on the system configuration.
Keywords: Teoria do funcional de densidade; Perovskita; CIENCIAS EXATAS E DA TERRA: FISICA: FISICA DA MATERIA CONDENSADA: ESTRUTURA DE LIQUIDOS E SOLIDOS CRISTALOGRAFIA; CIENCIAS EXATAS E DA TERRA: FISICA: FISICA DA MATERIA CONDENSADA: PROPRIEDADES MECANICAS E ACUSTICAS DA MATERIA CONDENSADA; DFT; Perovskite; Difração de raio-x; Altas pressões